Spontaneous pituitary adenoma occurring after resection of a Rathke's cleft cyst. (November 2016) - Chaudhry, Nauman S.; Raber, Michael R.; Cote, David J.; Laws, Edward R.
Highlights: There are rare reports of multiple lesions arising concomitantly in the sella. There are no reported cases of pituitary adenoma following prior resection of Rathke's cleft cyst (RCC). We present a patient who had a RCC and later developed a pituitary adenoma. Abstract: Rathke's cleft cysts (RCC) are benign cystic lesions that originate from remnants of the epithelial lining of Rathke's pouch. RCC are known rarely to occur together with a concomitant pituitary adenoma. Here, we report a patient with a pituitary adenoma arising in the same location as a previously-resected RCC, 3 years post-operatively, and review the literature of "collision" sellar lesions. Consecutive transsphenoidal operations from a single-center between 2008 and 2016 were reviewed to identify patients with pituitary adenoma arising after surgical resection of RCC, and a systematic search of the literature was also performed to identify such patient reports, as well as reports of concomitant pituitary adenoma and RCC. Of 837 transsphenoidal operations from our own experience, one patient with pituitary adenoma occurring after RCC resection was identified and is reported here. A systematic review of the literature resulted in identification of 34 patients with concomitant RCC and pituitary adenoma and no incidents of pituitary adenoma occurring after resection of RCC. Concomitant occurrence of RCC and pituitary adenoma was more commonly diagnosed in women (61%), at a median age of diagnosis of 44 years. The RCC histological analysis in these patients consistently described ciliated columnar or cuboidal epithelium. Although rare, the presence of a new, pathologically-distinct lesions in the sella after prior surgical treatment, is possible. During post-operative monitoring, physicians should consider that what appears as a "recurrent" lesion may actually be growth of a new and entirely different lesion.